The Meaning of Prayer for Young Catholic Religious Sisters of the Congregation of the Blessed Virgin Mary - Carolus Borromeus Mulyatno; Veronika Puji Astuti (International Journal of Qualitative Research, 2026)
This qualitative research aims to obtain data on the meaning of prayer for young Catholic religious of the Congregation of Blessed Virgin Mary of Amersfoort of Samarinda Province.  The data collected included three things that were formulated in three questions as research instruments. First, what kind of prayer atmosphere is experienced? Second, what are the benefits of prayer? Third, what are the fruits of prayer experienced?  The three questions became research instruments used to collect data using the Focus Group Discussion (FGD) method.  The data were analyzed using the Interpretative Phenomenological Analysis (IPA) theoretical framework. An important finding of this study is that the dominant atmosphere of prayer is silence, calm, full of gratitude, and close to God. The benefits of prayer are felt as a blessed experience to relate, communicate, and be with God. Prayer is also felt as a graceful experience that is very helpful for processing personal struggles and affirming steps in living life in fulfilling vocations and missions as a religious. The fruits of prayer include deeper self-knowledge, the experience of being loved by God, the experience of being supported by God's grace, the spiritual support of the Blessed Virgin Mary, the spirit of life renewal, and experiencing the figure of God as a Father who treats longing for a male figure or a father.